Improvement of Job Satisfaction Based on Work Motivation, Work Environment, Competence and Compensation for Hospital Employees - Nursaid Nursaid; Nurul Qomariah; Abadi Sanosra; Eko Budi Satoto; Artiantyo Wirjo Utomo (Indonesian Journal of Law and Economics Review, 2020)
This study aims to determine the factors that can increase employee satisfaction at the Regional Hospital dr. Sobandi Jember. These factors include work motivation, work environment, and compensation and HR competencies. The population in this study is 226 employees who will also be used as research samples. Thus this research is also called census research. This type of research is quantitative research. Data analysis techniques using structural equation modeling with PLP Warp software that tests the validity and reliability of measuring instruments, as well as model fit and path analysis test. The results showed that the motivation variable with a coefficient of 0.281 affected employee satisfaction. Work environment variables with a coefficient of 0.162 affect employee satisfaction. HR competency variable with a coefficient value of 0.010 does not affect employee satisfaction. While the compensation variable with a coefficient of 0.681 affects employee satisfaction.